Muslim American Cyber Contestations between Scholars and Activists Debating Racism, Islamophobia and Black Lives Matter - Latif, Jibril (Journal of religion, media and digital culture, 2018)
Over the last half-century, African Americans have been supplanted as the representational face of Islam in America by an immigrant population they initially perceived as obsequious to power and unconcerned with seeking redress to their historical grievances. Recently, however, a widespread cognizance of this strategic miscalculation coupled with the precipitous rise of Islamophobia in the Trump era has younger descendants of Muslim immigrants identifying with the left, combating Islamophobia as a type of racism in intersectional solidarity with other social justice platforms like the Black Lives Matter movement (blm). Thus, when fundamental disagreements emerged at the ris conference in late 2016 over endorsing the non-profit blm entity, they sparked robust social media debates. This paper analyzes those inter-communal negotiations as they played out on the Facebook pages of Muslim scholars, associating discourse models with contestations of community members negotiating the boundaries involved with integrating the heterogeneous discourses of antiracism.